USE OF ESSENTIAL OILS IN MEDICINE AND SPA (World Science, 2021)
This article is a short historical overview of the use of essential oils and aromatherapy from ancient times until present days. It presents brief characterization of essential oils and the possible ways of application as well as the main methods of their extraction. The focus is on aromatherapy as a main form of essential oil use, the mechanism of action of these oils and the basic biological and physiological effects on the human organism. The main modes of their application are described together with some possible side effects. Special attention is paid to the use of aromatherapy in spa.Conclusion: Aromatherapy can be used as a means of restoring the balance and harmony between the individuals and the environment they live in by helping the organism with managing the stress.Essential oils are not panacea, but are an excellent and efficient way of improving the mood, conquering the emotions, and balancing the hormones. There is a need of current and more thorough studies on the effect of essential oils and aromatherapy on the different organs and systems, and in many diseases and functional conditions.